Synthesis of Printed Hollow Fiber Membranes Urea as a Membrane Candidate Hemodialysis - Djunaidi, Muhammad Cholid; Ayuningrum, Denandha Putri; Maharani, Nesti Dwi; Khabibi, Khabibi; Pardoyo, Pardoyo; Raharjo, Yanuardi; Susanto, Heru; Filardli, Abdullah Malik Islam (Universitas Gadjah Mada, 2024)
Chronic kidney failure is a disease that affects the world's population and an alternative solution is hemodialysis. Hemodialysis is the process of cleaning the blood from urea and creatinine through a semi-permeable membrane in the form of a hollow fiber membrane (HFM) with the following advantages: flexible and low energy requirements. The weaknesses of commercial hemodialysis membranes are that they are hydrophobic, chemical resistant, and low biocompatibility. This research uses a membrane of polysulfone combined with eugenol and polyethylene glycol (PEG) or polyethylene glycol diglycidyl ether (PEGDE). Eugenol has allyl, hydroxy, and methoxy groups which are derived from polyeugenol via allyl groups and from polyeugenol to polyeugenoxy acetic acid via hydroxyl groups. The resulting molecularly imprinted membrane (MIM) in the form of hollow fiber has better porosity, absorption, flux values and is highly selective in transport, with the order of selectivity, namely urea > creatinine > vitamin B12.